(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Kinesiology tape is a commonly used non-pharmacological, pain alleviating treatment modality and its usage is being continually expanded into differing clinical settings such as the reduction of post-operative swelling and injury rehabilitation. At present, it is not possible to customize the mechanical properties of the tape to individual patients or usage scenarios. This paper presents the novel design and method of 3D printing lattice structures directly onto kinesiology tape in order to obtain tailorable mechanical properties, using an economical printing system and materials that are appropriate for a clinical setting.